60 Inhaled nitrous oxide for distressing procedures in children: a systematic review. (21st October 2022) - Poonai, Naveen; Creene, Christopher; Dobrowlanski, Aldo Ariel; Geda, Rishika; Hartling, Lisa; Ali, Samina; Bhatt, Maala; Trottier, Evelyne D; Sabhaney, Vikram; O'Hearn, Katie; Osmond, Martin; Jain, Rini
Abstract: Background: Inhaled nitrous oxide (N2 O) is a potentially effective agent for pain and procedural distress in children but questions remain regarding indication specific effectiveness. Objectives: Our objective was to synthesize the evidence for N2 O in children and youth regarding procedural distress, pain, and adverse events (AEs). Design/Methods: We performed electronic searches of MEDLINE, EMBASE, Google Scholar, CINAHL, conference proceedings, and trial registries. We included randomized trials of N2 O in children and youth 0-21.99 years that reported procedural distress or pain. Methodological rigor and quality of evidence were evaluated using the Cochrane Collaboration's Risk of Bias tool and the Grading of Recommendations Assessment, Development, and Evaluation system, respectively. Where meta-analysis wasn't possible, we summarized results using Tricco et al.'s classification system of "favorable" or "unfavorable" (p<0.05), or "neutral" (p> 0.05). Results: We included 29 trials, involving 2, 404 children aged 3 weeks-21 years. The overall quality of evidence for distress and pain was "low" and "moderate", respectively. For venous cannulation (n=12), three meta-analyses were possible: A) pain was significantly lower with 70% N2 O versus eutectic mixture of local anesthetics (EMLA) (mean difference: -16.5; 95% CI: -28.6 to -4.4; p=0.008; 85 participants; 3 trials; I 2 = 0%); B) pain was not significantly different with 50% N2 O alone versus EMLA (mean difference: -0.4; 95% CI: -1.2 to 0.3; p=0.26; 65 participants; 2 trials; I 2 = 15%); C) combination 50% N2 O plus EMLA was significantly better than EMLA alone (mean difference: -1.2; 95% CI: -2.1 to -0.3; p=0.007; 65 participants; 2 trials; I 2 = 43%). For pain and distress during laceration repair (n=5), N2 O was deemed "favorable" versus subcutaneous lidocaine, oxygen, or oral midazolam, but "neutral" versus intravenous ketamine. For pain and distress during fracture reduction (n=3), N2 O was deemed "neutral" versus combination intramuscular meperidine plus promethazine, intravenous lidocaine, or combination intravenous ketamine plus midazolam. For pain and distress during lumbar puncture (n=1), N2 O was deemed "favorable" versus oxygen. Higher concentrations of N2 0 were associated with more AEs per participant: 6.7% (1/15), 13.7% (64/468), and 25.3% (56/221) with 30%, 50%, and 70% N2 O, respectively. The most common AEs were nausea and agitation (both 3.5% [40/1128]). There were no AEs requiring resuscitative measures. Conclusion: N2 O is a potentially effective agent for reducing procedural distress and pain in children, although high quality evidence is lacking. Most data exist for venous cannulation where safety and efficacy at reducing pain are optimized with combining 50% N2 O and topical anesthetic cream. For laceration repair, there is considerably less data. Still, N2 O appears to be superior to oral midazolam but equivalent to intravenous ketamine.